2016
DOI: 10.1007/978-3-319-41334-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol and Its Role in Chronic Diseases

Abstract: Tocotrienol is a member of vitamin E family and is well-known for its antioxidant and anti-inflammatory properties. It is also a suppressor of mevalonate pathway responsible for cholesterol and prenylated protein synthesis. This review aimed to discuss the health beneficial effects of tocotrienol, specifically in preventing or treating hyperlipidaemia, diabetes mellitus, osteoporosis and cancer with respect to these properties. Evidence from in vitro, in vivo and human studies has been examined. It is revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 164 publications
0
31
0
1
Order By: Relevance
“…T3 has been shown to possess the potential as a hypocholesterolemic agent [38]. It is known as an inhibitor of the mevalonate pathway responsible for the synthesis of cholesterol and other isoprenoids.…”
Section: Effects Of Tocotrienol On Lipid Metabolismmentioning
confidence: 99%
“…T3 has been shown to possess the potential as a hypocholesterolemic agent [38]. It is known as an inhibitor of the mevalonate pathway responsible for the synthesis of cholesterol and other isoprenoids.…”
Section: Effects Of Tocotrienol On Lipid Metabolismmentioning
confidence: 99%
“…Tocotrienol, a member of vitamin E family in addition to tocopherol, has been shown to exhibit bone protective action in various animal bone loss models [ 14 , 15 , 16 ]. Homologues of tocotrienol, namely alpha-, beta-, gamma-, and delta-tocotrienol, are available in mixtures derived from plant sources [ 17 , 18 ]. Oil derived from palm kernel, annatto seed and rice bran is rich in tocotrienol [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies were reported pointing out that TTs, specifically γ‐ and δ‐TT, are endowed with a significant anticancer activity against different tumors (Aggarwal, Sundaram, Prasad, & Kannappan, ; Cardenas & Ghosh, ; Chin et al, ; Henderson et al, ; Malavolta et al, ; Meganathan & Fu, ; Peh et al, ). In addition to their antioxidant and anti‐inflammatory properties, the anticancer effects of these compounds were also shown to be related to their interaction with different intracellular signaling pathways involved in the mechanisms of proliferation, apoptosis, angiogenesis, and metastasis (Galli & Azzi, ; Kannappan, Gupta, Kim, & Aggarwal, ; Miyazawa, Shibata, Nakagawa, & Tsuzuki, ; Nesaretnam, ; Sailo et al, ; Shanmugam, Warrier, Kumar, Sethi, & Arfuso, ; Sylvester et al, ; Zingg, ).…”
Section: Anticancer Properties Of Tts: In Vitro and In Vivo Studiesmentioning
confidence: 99%